Sinteza Pavlove teologije o pravičnosti in opravičenju - Lülik, Benjamin (Edinost in dialog, 2024)
This paper explores the Apostle Paul's teachings on righteousness and justification, emphasizing forensic, covenantal, apocalyptic, and sacramental aspects of his theology. Analysing key passages in Romans and Galatians, it integrates insights from contemporary theologians Douglas Campbell, N.T. Wright, and Pope Benedict XVI. Central to Paul's theology is the concept of justification by faith and the transformative power of divine grace. This study highlights the theological richness of Paul's teachings, while also acknowledging their ecumenical potential. By synthesizing these perspectives, the paper offers a comprehensive understanding of Pauline righteousness and its enduring relevance in contemporary Christian life.
Keywords: apocalyptic; apokaliptično; covenant; faith; grace; justification; milost; odrešenje; opravičenje; Pavel; pravičnost; preobrazba; righteousness; sacraments; salvation; transcendence; transformation; vera; zakramenti; zaveza